"Peace, Salaam, Shalom": Functions of Collective Singing in U.S. Peace Activism - Jeneve R. Brooks (Music and Arts in Action, 2010)
This article adds to the emerging literature on music and conflict transformation by highlighting the use of collective singing by U.S. peace activists when engaged in various peace movement activities. Based on preliminary findings from focus groups with peace activists and in-depth interviews with notable peace musicians, this article asserts that group sing alongs have helped in mobilizing U.S. peace activism efforts over the last four decades through three specific functions: 1) extending frames to include broader peace and justice issues; 2) strengthening cognitive liberation amongst activists; and 3) appealing to and reinforcing a wide range of activists’ emotions. Although the group sing along may seem passé within some activist circles, this article affirms that it has served and continues to serve key functions in the peace protest repertoire. The article concludes with a discussion of issues that threaten the future of group sing alongs and urges conflict transformation practitioners and peace movement leaders to recognize the utility of collective singing so as to reinvigorate this long-standing tradition within social movements.